Investigation of aliphatic and polycyclic aromatic hydrocarbons in surface sediments of Brunei Bay, East Malaysia - Pang, Swee Yun; Suhaimi, Suratman; Tay, Joo Hui; Norhayati, Mohd Tahir (Asian J. Chem, 2021)
The surface distributions of aliphatic hydrocarbons and polycyclic aromatic hydrocarbons (PAHs) were investigated from coastal sediments of Brunei Bay, southern South China Sea. The concentrations of total n-alkane (TNA) and 16 USEPA priority PAHs ranged from 0.67 to 9.88 μg/g and 4.72 to 102 ng/g, respectively. Principal component analysis (PCA) clustered the hydrocarbons in surface sediments according to their relationship and geographical locations, anticipated to the inputs and activities in proximity. Biomarker diagnostic ratios revealed that biogenic n-alkane inputs in the coastal sediments are exported from the fluviomarine and mangrove swamp environment, while the PAHs inputs are derived from mixed petrogenic and petroleum combustion residues. Overall, the level of PAHs in the study area is between low to moderate, based on the comparison with other areas worldwide.